1970
DOI: 10.1103/physrevlett.24.615
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Existence of aZ*

Abstract: It should be noted that d(a t 2 +a 2 2 )/dt and dSl/dt both behave like {a^a^) 2 as one approaches the point of bifurcation. 7 The singularity which this expression manifests at £2 2 = 4B n (where dynamical instability sets in) is spurious: Eq. (15), without the substitution (16), leads to the result a= £2±(0.4Z?£2 5 )Results of a phase-shift analysis with and without the use of a Regge-pole model in K + p elastic scattering from 0.86 to 1.95 GeV/c are described. We have obtained four possible solutions, all o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1970
1970
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Hashimoto [15] observed a resonance-like structure in the T=0 D3/2 wave which had been seen before [19,25,26]. While we see a loop in the Argand diagram, it is less pronounced than what he saw.…”
Section: Analysis Of Hashimotomentioning
confidence: 64%
See 2 more Smart Citations
“…Hashimoto [15] observed a resonance-like structure in the T=0 D3/2 wave which had been seen before [19,25,26]. While we see a loop in the Argand diagram, it is less pronounced than what he saw.…”
Section: Analysis Of Hashimotomentioning
confidence: 64%
“…Leaving aside many of the earlier analyses [16,17,18,23,24,25,26,27,28] there are three modern analyses with which we compare.…”
Section: A Other Work For T=1mentioning
confidence: 99%
See 1 more Smart Citation
“…S. Kato et al 22 obtained four possible solutions from a phase shift analysis of K + p elastic scattering and on the basis of Argand diagrams concluded on a possible mass of the Z * around 1.9 to 2 GeV and Γ ∼ 130 − 250 MeV in the P 13 partial wave. This work was followed by two articles by Aaron et al 23 which reported evidence for the Z * 's in the D 03 , S 01 and P 01 partial waves using Argand diagrams and speed plots.…”
Section: Seventies and Eightiesmentioning
confidence: 99%
“…Additional work relevant to this section can be found in Kato et al (1969), Neville (1969), Schmid (1969b), Schwimmer (1969), and Yellin (1969c) Footnotes for Section VIII 8a) We e:mphasize that these duality diagrams are not the dual diagrams connected with the singularity structure of Feynman diagrams.…”
Section: C Breaking Dualitymentioning
confidence: 99%